Structure of Mathematical Research - Ghimire, Santosh; Khadka, Shreeram; KC, Durga Jang (Nepal Journal of Mathematical Sciences, 2021)
In this paper, we discuss about the structure of various components of mathematical research. We mainly focus on the structure of PhD proposal, PhD thesis and research article. We describe in detail about the standard structure of these components in the context of mathematics.